ASSESSING THE RESPONSIBILITY TO REBUILD COMPONENT IN POST-GADDAFI LIBYA - Krisetya, Beltazar A; Utomo, Tri Cahyo; Basith Dir, Andi Akhmad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The 2011 military intervention in Libya is the first interventionbacked by the United Nations (UN) referencing the Responsibilityto Protect (R2P) with UN Security Council (UNSC) Resolution1970 and 1973 as legal basis. R2P consists of three components:responsibility to prevent, responsibility to react, and responsibilityto rebuild. The intervention was regarded as a success by NATO,the mandate holder. However, the mandate only covers thecomponent of preventing and reacting of R2P, leaving therebuilding (post-intervention strategy) unchecked. This researchattempts to identify the extent of Responsibility to Rebuildimplementation by international community after 2011 intervention.Case study and descriptive approach used found out that therebuilding process, particularly in security, justice, and economyaspect has yet to be restored in Libya, and not fulfilling thedemands set by responsibility to rebuild.